Is Organizational Culture a key driver to successful long-term innovation management? - Wilson, Bryce (2017)
This piece of research aims to answer the research question: Is Organizational Culture a key driver to successful long-term innovation management? An initial literature review on topics relevant to the question including managing change, managing innovation, and organizational culture was done in order provide a background of what research has already been done on the topics. The case study research model was utilized with a combination of semi-structured interviews, and data analysis on two separate companies, Amazon, Inc., and Valassis Communications Inc. The findings presented in this research show support that organizational culture is a crucial factor in successfully managing innovation.